Sistem Informasi Pembayaran SPP dan Absensi Siswa Berbasis SMS Gateway - Muhammad Taufiq Rustam; Lahmudin Sipahutar; Wirhan Fahrozi (STMIK Budi Darma, 2020)
The development of technology today is very rapid and many innovations created such as administrative information systems have been used by many parties, both organizations and educational institutions. Especially at elementary level educational institutions that still use manual administrative information systems, therefore, to help administrators and teachers in matters relating to the SPP Payment Process and Student Abstentions which are more effective and efficient by using an sms gateway based application. In addition, there is still a lack of information from the school to parents or guardians of students regarding payment transactions and information on arrears in tuition fees and student attendance. The results of the research conducted resulted in a tuition payment application and student attendance